2021
DOI: 10.1371/journal.pone.0254236
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables contamination by heavy metals and associated health risk to the population in Koka area of central Ethiopia

Abstract: Contaminated soil and vegetables have continued to instigate threat to human health globally and specially in developing countries. This study was aimed to determine concentrations of certain heavy metals in soil and vegetables (cabbage and tomato) from Koka area of central Ethiopia using Inductively Coupled Plasma Optical Emission Spectrophotometer (ICP-OES). The amounts of As, Pb, Cd, Zn, Cu, Hg and Co detected in soil samples were found to surpass the reference values for agricultural soil. Similarly, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 55 publications
3
7
0
Order By: Relevance
“…As depicted in Table 4 , the findings of the current study are compared with those of other researchers in other horticultural farms located in the Central Ethiopian Rift Valley. Accordingly, the recorded values for all eight heavy metals were much higher in Modjo and Koka vegetable farms, except for Pb, as reported by Gebeyehu and Bayissa [ 48 ] and Bayissa and Gebeyehu [ 49 ]. However, Samuel et al [ 47 ] found that soils collected from vegetable farms in the Hawassa industrial zone had more or less equal values for As, lower values for Pb and Cd, and considerably higher values for Zn, Cu, Ni, and Cr than the current study.…”
Section: Resultssupporting
confidence: 69%
“…As depicted in Table 4 , the findings of the current study are compared with those of other researchers in other horticultural farms located in the Central Ethiopian Rift Valley. Accordingly, the recorded values for all eight heavy metals were much higher in Modjo and Koka vegetable farms, except for Pb, as reported by Gebeyehu and Bayissa [ 48 ] and Bayissa and Gebeyehu [ 49 ]. However, Samuel et al [ 47 ] found that soils collected from vegetable farms in the Hawassa industrial zone had more or less equal values for As, lower values for Pb and Cd, and considerably higher values for Zn, Cu, Ni, and Cr than the current study.…”
Section: Resultssupporting
confidence: 69%
“…As a result, the HI of the different metals studied was determined using Eq (3) . HI values below unity (HI < 1) signifies no significant risk of non-carcinogenic effects while HI values above unity (HI > 1) imply the probability of non-carcinogenic health risk occurring in the exposed population [ 35 , 37 ]. whereas an HI greater than 10.0 indicates a substantial chronic health impact [ 35 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…in the exposed population [35,37]. whereas an HI greater than 10.0 indicates a substantial chronic health impact [35,38].…”
Section: Plos Onementioning
confidence: 99%
“…Also, heavy metal contamination and public health problems are more pronounced in developing nations compared to developed ones. [37][38][39][40] Hence, human health risk assessment of heavy metals through commonly consumed vegetables and fruits is necessary. The main objectives of the study were, (1) to investigate the soil quality and selected heavy metal contamination in the study area, (2) to investigate heavy metal accumulation (Pb, Cd, As and Hg) in locally grown 24 different kinds of vegetables and fruits, and (3) to evaluate the potential health risk caused by these vegetables and fruits.…”
Section: Introductionmentioning
confidence: 99%